Impact of defatting and drying methods on the overall liking and sensory profile of a cereal bar incorporating edible insect species - Ribeiro, José Carlos; Santos, Carla; Lima, Rui Costa; Pintado, Manuela E.; Cunha, Luís Miguel (Future foods : a dedicated journal for sustainability in food science, 2022)
•Ethanol was the best solvent to defat T. molitor.•Bar with defatted T. molitor could have legal claim of ‘high in protein’.•Oven-dried insects associated with negative odor/flavor attributes.Microwave-drying led to better liking and sensory profile than oven-drying.•Defatting hindered negative odor/flavor attributes and increased liking. It is necessary to develop products with desirable sensory properties in order to increase the acceptance of insect-based products by Western consumers. In this work, the impact of defatting on the sensory properties of cereal bars with yellow mealworm (Tenebrio molitor) larvae, in addition to the impact of different drying methods and different species (T. molitor and house cricket Acheta domesticus) were assessed. A model cereal bar incorporating oats, dried and dehydrated fruits was developed as well as four additional formulations with insect flour: defatted (Soxhlet method with ethanol) mealworm (TM_D), microwave (TM_MW) or oven dried (TM_O) mealworm and oven dried cricket (AD_O). A panel of 99 consumers rated overall liking and willingness to buy (9-point scale), and profiled the bars using a Check-All-That-Apply ballot. The bars with defatted or microwaved mealworm had similar liking and willingness to eat scores in comparison with the control bar. Conversely, bars with oven-dried insects had worse evaluations and were associated with negative attributes related to odor and flavor, which were hampered by defatting or microwave-drying. This study highlights how different processing methods can be applied in order to increase the sensory liking of insect-based products and also provides information on their sensory characterization.